Applied econometric time series - Enders, Walter 1948- (Wiley, 2015)
"Applied Econometric Time Series, 4th Edition demonstrates modern techniques for developing models capable of forecasting, interpreting, and testing hypotheses concerning economic data. In this text, Dr. Walter Enders commits to using a learn by doing approach to help readers master time series analysis efficiently and effectively."--Provided by publisher.